BAWASLU DI RANAH KEKUASAAN (STUDI KASUS KEPALA DAERAH SEBAGAI KETUA KAMPANYE) - Wirawan, Arya Bintang; Bandiyah, Bandiyah; Erawan, I Ketut Putra (Jurnal Nawala Politika, 2019)
ABSTRACT The involvement of head of district often occurs in every general election indicates a violation against the law of election. In Bali’s Province general election in 2018, found an indication that Badung Regent Nyoman Giri Prasta had already inside one of the campaign structure of Wayan Koster-Cok Ace, who became their head of the campaign. This research examines the effort of Bawaslu to proceed against this case. New Separations of Power and State in Society was a theory in this research which occur the effort of Bawaslu as state support institutions.. This research explains that Bawaslu effort in proceeding a violation against election law in administrative and ethical codes. Balinese Bawaslu couldn’t proceed the allegation findings, showing that Bawaslu has no authority to proceed this case due to their existence only as state support institutions that require aid from other relevant institutions which handle the violation against election law. Keywords : Violation of The Involvement of Regional Heads, District Head Election, Bawaslu